Development of a wearable live-feedback system to support partial weight-bearing while recovering from lower extremity injuries - Bril, A. T.; David, V.; Scherer, M.; Jagos, H.; Kafka, P.; Sabo, A. (Procedia Engineering, 2016)
Lower-body physical rehabilitation therapies and technologies are inevitably linked to the sports world. Partial weight-bearing is a common measure that accelerates the healing process following lower-body surgeries or fractures. In order to improve the compliance with this method, a smartphone application was developed. It provides the user with an audible and haptic biofeedback alarm when a predefined threshold is reached by the pressure sensors data of a pair of instrumented insoles. The preliminary results show that the alarm functionality works in accordance with the stipulations. The biofeedback also appears to have a positive effect on the amount of steps under the target weight.